2003
DOI: 10.1097/00005537-200309000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Follow‐Up of Pediatric Recurrent Respiratory Papillomatosis Managed with Intralesional Cidofovir

Abstract: Intralesional cidofovir is a useful adjunct for managing children with tenuous airways caused by previously uncontrolled papilloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 20 publications
1
57
0
3
Order By: Relevance
“…When used intravenously at this dose, cidofovir can cause nephrotoxicity and neutropenia (9). However, recent studies suggest that these side effects are limited to intravenous use, with no evidence of renal, hepatic or hematological toxicity when injected into papillomatous lesions of the larynx or trachea (10).…”
Section: Discussionmentioning
confidence: 99%
“…When used intravenously at this dose, cidofovir can cause nephrotoxicity and neutropenia (9). However, recent studies suggest that these side effects are limited to intravenous use, with no evidence of renal, hepatic or hematological toxicity when injected into papillomatous lesions of the larynx or trachea (10).…”
Section: Discussionmentioning
confidence: 99%
“…A number of adjuvant therapies have been proposed; however, in most cases, a cure is not achieved, only palliation. Cidofovir is one of the most common adjuvant drugs currently used in the treatment of RLP 5 and, despite the favorable results demonstrated in most studies, [13][14][15][16][17][18][19][20] administration and dosage regimens, as well as safety of cidofovir, are yet to be established in the treatment of this disease.…”
Section: Patientmentioning
confidence: 99%
“…Doses between 2.5 and 30 mg of cidofovir are reported in the literature, injected intralesionally or in the region of papilloma excision. Some studies have demonstrated favorable results, that is, remission or decreased severity of disease in most patients treated with cidofovir, [13][14][15][16][17][18][19][20] whereas other studies have not observed a significant improvement. 21,22 objectIve To evaluate the efficacy of local application of cidofovir in association with surgical treatment of RLP in children.…”
mentioning
confidence: 99%
“…Two patients initially responded to the therapy with a reduction in severity, but had return of their symptoms after the fifth injection, and the last patient had no response. In a study of 11 children who had previously required operative debulking to maintain airway patency, longitudinal follow-up for 6 years showed that 5 patients were disease free, and an additional 5 incurred a significant reduction in disease burden after intralesional cidofovir [59]. …”
Section: Therapeutic Applications Of Tbnimentioning
confidence: 99%